WHY DEMOCRACY HAS NO NEED FOR RELIGION? - Jokubaitis, Alvydas (Politologija, 2013)
The aim of the study was an analysis of two the conceptions of relationships between democracy and religion. One of these conceptions was created by Alexis de Tocqueville. He thought that democracy needs religion as an element that enriches it and helps in removing some negative tendencies inherent in this form of government. He understood that democracy was coalesced with the philosophies that were alien to religion, however, he demanded an alliance of democracy and religion. The other object of philosophical analysis is John Rawls. The theories of this author show an important change in the relationship of religion and democracy, which stems from the fact that he equates religion with philosophy. The political liberalism of Rawls helps us understand why democracy as a form of government has no need of religion. The political liberalism of Rawls reveals an important aspect of relationship between democracy and religion. He differs from Tocqueville by thinking that this form of government is not inherently merged with religion. Democratic state aspires to be neutral towards religion. Believers can be honest democrats, but this regime is indifferent in respect of religion. Democrats are on the side of worldly immanence, and believers side with religious transcendence. These two competing attitudes create a tension between religion and democracy. The solution of this tension, proposed by Rawls, consists in the equalization of philosophy and religion; it reveals that democracy is indifferent towards religion. The equalization of the status of philosophy and religion highlights the fact that this form of government is neutral in respect of the conception of God. This negates the Tocquevillian conception of the role of religion in democracy. Democracy can function without the support of traditions of religious thought.